Autoantibodies to neurotransmitter receptors and ion channels: from neuromuscular to neuropsychiatric disorders - Martinez-Martinez, Pilar; Molenaar, Peter; Losen, Mario; Stevens, Jo; De Baets, Marc; Szoke, Andrei; Honnorat, Jerome; Tamouza, Ryad; Leboyer, Marion; van Os, Jim; Rutten, Bart (Frontiers in Genetics, 2013)
Changes of voltage-gated ion channels and ligand-gated receptor channels caused by mutation or autoimmune attack are the cause of so-called channelopathies in the central and peripheral nervous system. We present the pathophysiology of channelopathies of the neuromuscular junction in terms of loss-of-function and gain-of-function principles. Autoantibodies generally have reduced access to the CNS, but in some cases this is enough to cause disease. A review is provided of recent findings implicating autoantibodies against ligand–activated receptor channels and potassium channels in psychiatric and neurological disorders, including schizophrenia and limbic encephalitis. The emergence of channelopathy-related neuropsychiatric disorders has implications for research and practice.